O efeito faraday: da atividade óptica natural ao elétron. - MATOS, Bruno César da Silva (2024)
In this paper we analyze the mechanisms that contributed to the theoretical description of the magnetic rotatory effect on light, discovered by Michael Faraday. We indicate the origin and inspiration of these mechanisms from the theory of birefringence and natural optical activity, in the context of the elastodynamic theory of light, started by Fresnel in the first half of the nineteenth century. Then, their improper incorporation in the optical-electromagnetic unification program, in the work of Maxwell, the gradual transition to the context of the electromagnetic theory of light and, finally, its purification by the electron theory on the eve of the birth of Bohr’s atom.